The associations of sequence variants in DNA-repair and cell-cycle genes with cancer risk: genotype–phenotype correlations. (20th May 2009) - Hall, Janet; Marcel, Virginie; Bolin, Celeste; Fernet, Marie; Tartier, Laurence; Vaslin, Laurence; Hainaut, Pierre
Abstract : DNA-repair systems maintain the integrity of the human genome, and cell-cycle checkpoints are a critical component of the cellular response to DNA damage. Thus the presence of sequence variants in genes involved in these pathways that modulate their activity might have an impact on cancer risk. Many molecular epidemiological studies have investigated the association between sequence variants, particularly SNPs (single nucleotide polymorphisms), and cancer risk. For instance, ATM (ataxia telangiectasia mutated) SNPs have been associated with increased risk of breast, prostate, leukaemia, colon and early-onset lung cancer, and the intron 3 16-bp repeat in TP53 (tumour protein 53) is associated with an increased risk of lung cancer. In contrast, the variant allele of the rare CHEK2 (checkpoint kinase 2 checkpoint homologue) missense variant (accession number rs17879961) was significantly associated with a lower incidence of lung and upper aerodigestive cancers. For some sequence variants, a strong gene–environment interaction has also been noted. For instance, a greater absolute risk reduction of lung and upper aerodigestive cancers in smokers than in non-smokers carrying the I157T CHEK2 variant has been observed, as has an interaction between TP53 intron 3 16-bp repeats and multiple X-ray exposures on lung cancer risk. The challenge now is to understand the molecular mechanisms underlying these associations.